2017
DOI: 10.21859/sija-1202180
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Fitness Exercise, Mental Exercise and Mindfulness Exercise on Static and Dynamic Balance in Elderly Women

Abstract: Objectives Elderly are exposed to balance dysfunction. This research aims at investigating the effect of physical exercises, mindfulness and mental training on static and dynamic balance in elderly women. Methods & Materials The participants included 60 women in the age group of 60-75 years who were categorized into four groups randomly (three experimental groups "mindfulness, mental training, and physical exercises" and a control group, with 15 members in each group. To measure dynamic and static balance, Ber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Physical activity also provides an opportunity for older people to have an active and independent life, to reduce disability and to improve their quality of life [17]. Studies have shown that different exercise training mods, for example resistance and endurance exercises, have positive effects on the static and dynamic balance, reaction time and strength of the elderly [18,19]. Some evidence suggests that resistance training with elastic bands increases functional performance and improves muscle mass in older people [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity also provides an opportunity for older people to have an active and independent life, to reduce disability and to improve their quality of life [17]. Studies have shown that different exercise training mods, for example resistance and endurance exercises, have positive effects on the static and dynamic balance, reaction time and strength of the elderly [18,19]. Some evidence suggests that resistance training with elastic bands increases functional performance and improves muscle mass in older people [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the present study showed that ETPS significantly improved motor balance and increased pain threshold in rats with AD. Authors believe that physiological adaptations to exercises can im-prove the utilization of motor units and increase the vitality of the motor cortex in elderly people (24) through the reduction of oxidative stress and sympathetic system activity (25) as well as the increase of neurotrophins (26). In line with the present study findings, physical activity had a significant effect on the improvement of static and dynamic balance in the elderly (24); exercise training had a significant effect on improving motor balance and quality of life (27), and modified exercises had significant pain relief effects (28); nevertheless, weight-bearing training did not have a significant effect on dynamic balance in elderly males (29).…”
Section: Discussionmentioning
confidence: 99%